Development of interactive learning media assisted by Articulate Storyline 3 based on Android to improve the ability to understand mathematical concepts at SMPN 3 Stabat - Fadila Khairunisa; Dian Armanto (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to determine the quality (validity, practicality and effectiveness) of the results of the development of android-based Articulate Storyline 3-assisted interactive learning media to improve the ability of students to understand mathematical concepts that have been developed. This research is research and development or RD (Research and Development) that uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects in this study are 30 students in grades VIII-2 SMPN 3 Stabat. The data collection techniques used in this study are interviews, observations, questionnaires and tests of mathematical concept comprehension ability. Based on the results of the validation of interactive learning media assisted by Articulate Storyline 3 based on android to improve the ability to understand mathematical concepts that have been developed by media experts and subject matter experts, an average percentage of 93% and 96.3% was obtained which was categorized as "very valid" or suitable for use. The average practicality presentation from the mathematics teacher's response of 94.5% was categorized as "very practical". And obtained an average percentage of effectiveness from student responses of 94.75% which was categorized as "very effective". Learning media is said to be effective judging from the completeness of students' learning classically reaching 90%. Percentage Increase in the students' answer process is seen from the increase in the test of mathematical concept comprehension based on the N-Gain score test of 0.77% which is categorized as high. Thus, based on the results of the validation of media experts, material experts, junior high school mathematics teachers and student responses, the android-based interactive learning media Articulate Storyline 3 to improve the ability to understand mathematical concepts has been developed feasible and tested for validity, practicality and effectiveness to be used in learning activities to improve comprehension skills students' mathematical concepts.